PERANAN BADAN USAHA MILIK DESA DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT DESA DI DESA SUKAJAYA, KABUPATEN SUKABUMI - Anugrah, Ce Mulya Rizki; Suciati, Fithri; Safitri, Niken (2021)
One way to improve the economy through community empowerment is to form a village-owned business entity or better known as BUMDes. Many BUMDes are unable to show their existence as one of the driving wheels of the economy of a village, unlike other BUMDes, the BUMDes Terus Jaya Sehati, which is located in Sukajaya Village, Sukabumi Regency, can manage the potential of its village well. This is of course interesting to study because while other BUMDes have problems with several conditions,the BUMDes continue to Jaya Sehati have been advancing to contribute to village empowerment and development. The method used is a qualitative research method with a descriptive approach pattern which is carried out through direct and indirect observations, conducting interviews, and documenting the object under study. The results of the study show that BUMDes has an important role in community empowerment in Sukajaya Village, some of which are buying produce from BUMDes Mart and providing training on making bamboo containers for Mochi Cakes and then the results are sold and bought by BUMDes for remarketing. One of the roles played by BUMDes is contributing to the village title, from previously holding the title of the underdeveloped village to developing village.